Automatic Game World Generation for Platformer Games Using Genetic Algorithm - Ali Sofyan Kholimi; Ahmad Hamdani; Lailatul Husniah (Proceeding of the Electrical Engineering Computer Science and Informatics, 2018)
Most of the games rely on the game designer to design the level and environment. Increasing of game environment space scale followed by increasing of time and cost. Procedural Content Generation (PCG) is a method to solve this problem by generating a game environment space. In this paper, a PCG method proposed using a genetic algorithm approach to solve the problem in generating game environment. Transition graph adapted in the proposed method to make PCG generate difficulty level. The Index-based approach used to display the biome sequence. This approach displays the biome according to its index in the sequence.